The Influence of The Use of Learning Media, Interpersonal Communication, Instructional Communication on The Level of Emotional Intelligence - Laura Abigail Christie Boseke; Ilona Vicenovie Oisina Situmeang (Ridwan Institute, 2023)
This research aims to determine the magnitude of the influence of learning media, interpersonal communication, and instructional communication on student absorption levels. This research is quantitative research with data distribution through surveys. People with autism need proper education with appropriate learning methods, therefore inclusive schools are formed which are able to support education for children with special needs. The results of this research are that there is a significant influence between the variables of instructional communication, interpersonal communication, and learning media with emotional intelligence.